"There are more important things to worry about": attitudes and behaviours towards leisure noise and use of hearing protection in young adults. (3rd June 2018) - Hunter, Abby
Abstract: Objective : Noise-induced hearing problems among young adults are increasing due to participation in loud activities. This study explored attitudes towards leisure noise, hearing protection, and perceived susceptibility to noise damage in young adults with no diagnosed hearing problems. Understanding attitudes and behaviours will assist with the future development of strategies to improve awareness and use of hearing protection. Design : A qualitative study. Study sample : Four focus groups, with 28 adults aged 18–35 years (6 male; 22 female; mean age 23 years). Results : Using framework analysis, five themes emerged. Earplug use occurred when participants had experienced previous temporary hearing damage (i.e. short-lived tinnitus or hearing loss). Others chose not to use earplugs because music venues are expected to be loud. Peer behaviours and opinions also had a strong influence over earplug use. A lack of knowledge of hearing-related damage resulted in a lack of concern for hearing health and other health conditions taking priority. Conclusions : The challenge is to present hearing health messages that are relevant and accessible to young adults. Music and entertainment venues must also take greater responsibility to protect the hearing of its customers by at least informing visitors of the dangers of loud music.